RF Front-End for RADAR - Tiago Domingos Martins (2021)
Synthetic Aperture Radar (SAR) is a technology used to record RF images, that are considerably insensitive to effects like dust, clouds, day light... By coupling RADAR theory with signal processing techniques, it is possible to obtain images with useful levels of resolution. Over the years, advances in the RADAR and signal processing domains, have made it possible to obtain increasingly better quality images. One such advance was the introduction of Software Defined Radio (SDR), as a way to replace a lot of the conventional radio hardware by flexible and effective software. But, even though, it substitutes a lot of the previously used hardware, there is still the need for some electronics to interface the SDR with radio antennas. These modules are commonly referred to as "RF front-ends". The SARIA experiment is a student project that intends to perform SAR, using a SDR based architecture. This experiment will be housed in a stratospheric balloon in the context of the BEXUS program. Two antennas, an inflatable antenna and a static reflector, shall be used for SAR sessions. With this setup in mind, a RF front-end will be required. This module is expected to adequately transmit and receive C-band signals, with a concern for low-power, low-cost and adjustable transmission gain. This thesis work describes the development of a suitable RF front-end for appli-cations with similar specifications to the ones exhibited in the SARIA experiment. The module contains a Transmission chain with adjustable gain and up to 30 dBm of output power; a Reception chain with a noise figure under 2 dB and switching between RX and TX contexts based on RMS power detection with a pulse repetition frequency of 1 kHz.